DOES ORGANISATION BEHAVIOUR AFFECT PERFORMANCE OF AUDITING FIRMS? - Javed, Sarfaraz (International Journal of Engineering Technologies and Management Research, 2018)
The study examines the effect of organizational behaviour on auditing firms’ performance. It investigates the influence of Software Technology and customer relationship management on financial performance of PwC, Deloitte and KPMG testing four hypotheses. The data was from secondary sources of financial reports and statements of PwC, Deloitte and KGPM (2011-2016) and statistica.com. Hypotheses were tested using multiple regression analysis and Pearson correlation. SPSS version 17 was used to perform the multiple regression analysis while Smart PLS version 3.2.6 was used to carry out SEM. The first hypothesis revealed that relatively customer relationship negatively predicted financial performance of PwC while software technology positively predicted the financial performance of PwC. Hypothesis two shows that customer relationship and software technology did not jointly and relatively predicted financial performance of Deloitte while in hypothesis three, customer relationship and software technology did not jointly predicted financial performance of KPMG and in hypothesis four, customer relationship management and software technology positively jointly influenced financial performance of both PwC and Deloitte. There have been few studies to made use of Structural Equation Model (SEM) to examine the organizational behaviour in the auditing firms. In this paper, SEM was used to test the effect of Software Technology and Cost on customer relationship on financial performance of the auditing firms. This paper contributes to the impact of organizational behaviour in the auditing firms.